The influence of organizational justice on employee performance mediated work engagement - Wahid Sumarjo; Haerofiatna Haerofiatna; Didit Haryadi (Institute of Computer Science (IOCS), 2024)
The ability of organizations to work effectively and efficiently to achieve their goals and to be successful is possible with employees, who are the most valuable human capital, good organizational management, and the application of modern management principles and functions. Optimally activating employee performance is a challenge for organizations. This study examines the mediating effect of work engagement on organizational justice and employee performance. The method used in this research is a quantitative method with a causality approach. The sample used was 43 respondents. The results of this study show that organizational justice partially influences employee performance and work engagement. In contrast, work engagement significantly affects employee performance, and as expected, engagement can mediate between organizational justice and employee performance